Multimodal Approaches for Canine Estrus Detection Through Vaginal Electrical Resistance, Vaginal Cytology, Vaginoscopy and Progesterone Profile - Sharma, Vasu; Sharma, Amit; Tyson; Ahuja, Ankit; Sharma, Akshay; Kumar, Pravesh; Sood, Pankaj (The Indian Journal of Animal Reproduction, 2026)
This study aimed to combine two or more techniques to achieve more precise and dependable results for estrous detection. For this, 54 healthy female dogs were evaluated for estrous detection through different diagnostic methods, including vaginal electrical resistance (VER), exfoliative vaginal cytology (EVC), vaginoscopy and serum progesterone profiling. Vaginal cytology during proestrus revealed a significant proportion of large intermediate cells (61.94±4.98%), followed by small intermediate cells (26.58±3.53%) and a low proportion of keratinized cells (6.38±4.82%). During estrus, kera tinized cells dominated (70.67±2.64%), alongside large intermediate cells (25.25±2.84%). VER values peaked during estrus (614.72±63.91Ω), while specific means recorded as 233.87±28.95 Ω in proestrus. Vaginoscopy revealed pink, con gested vaginal mucosa with vulvar edema during proestrus, transitioning to wrinkled, shrunken and pale mucosa with progressing crenulations during estrus, driven by hormonal changes. Serum progesterone levels increased steadily from 0.63 ± 0.15ng/mL in proestrus to 7.29±0.83 ng/mL during estrus. Hence, the combined application of these diagnostic methods provides a comprehensive framework for predicting the estrus stage and improving reproductive management in canines.